Merger negotiations and ex-post regret - Dennis Gärtner; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2007)
We consider a setting in which two potential merger partners each possess private information pertaining both to the profitability of the merged entity and to stand-alone profits, and we investigate the extent to which this private information makes ex-post regret an unavoidable phenomenon in merger negotiations. To this end, we consider ex-post incentive compatible mechanisms, which use both players' reports to determine whether or not a merger will take place and what each player will earn in each case. When the outside option of at least one player is known, the efficient merger decision can be implemented by such a mechanism under plausible budget-balance requirements. When neither outside option is known, we show that the potential for regret-free implementation is much more limited, unless the budget balance condition is relaxed to permit money-burning in the case of false reports.
Keywords: D82; L10; G34; 330; Mergers; Mechanism; Design; Asymmetric; Information; Interdependent; Valuations; Efficient; Mechanisms; Fusion; Asymmetrische Information; Rentabilität; Verhandlungstheorie; Theorie